PENGARUH TATA TERTIB ASRAMA TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI - Sianturi, Risma Brenda; Parijo, Parijo; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to find out whether there is an effect and how significant is the effect of boarding rules to the learning motivation of the students in studying economy in class X IIS SMA TBK. The form of this research is correlation research with interrelationship studies. The sample of this research is the 56 students of class X IIS SMA TBK. The method of taking the sample is by using descriptive method, where the data is collected by using a questionnaire which its validity and reliability has been tested. The technique of data analysis used is the program SPSS Vol.18. The result of this research shows that after doing the simple regression linear test to the students? learning motivation with the of X and Y, it can be said that boarding rules has a positive effect to the students? learning motivation with the regression equation to the variable of Y=15,963+0,554X with the effect size of 30,4%. By doing the hypothesis testing comparing the significance value with 0,05, the significance value of 0,000<0,05 is obtained, therefore, a conclusion can be made with Ho is rejected and Ha is accepted. Next by doing hypothesis testing comparing t count with t table, the value of t count with the value of 4,852>1,674 t table is obtained; hence, it can be concluded that Ho is rejected and Ha is accepted, meaning that there is a significant effect between ?Boarding Rules to the Students? Learning Motivation in studying Economy in Class X IIS SMA TBK?.Keywords: Boarding Rules, Students? Learning Motivation